Effectiveness of Transformative Learning on Spirituality in Palliative Care among Nursing Students: A Mixed Methods Study - Sukcharoen, Pilaiporn; Sakunpong, Nanchatsan; Sripa, Kantita (The Journal of Behavioral Science, 2020)
This study aimed to investigate the impact of transformative learning on spirituality in palliative care among nursing students in Thailand by applying an embedded mixed methods research design. The experimental group (n = 24) received the intervention based on the transformative learning to enhance spirituality in palliative care which was conducted group discussion after completing each transformative learning session. Meanwhile, the control group (n = 24) received a regular instructional model. The instrument’s reliability (Cronbach’s alpha) was .80. From the main quantitative analysis, the two-way repeated measures ANCOVA revealed that the level of spirituality in palliative care of the experimental group was higher than the control group after the experiment, and also two months after the experiment (p < .05). From the qualitative analysis, three themes of learning experience that emerged were- ability to develop awareness and faith, acceptance and compassion for fellow human beings, and spiritual nursing behavior. The outcome of the study was a model of transformative learning to enhance spirituality in palliative care, associated with the experience of nursing students. These findings could be applied to develop an instructional model of palliative care for nursing students.